1992
DOI: 10.1007/bf00210743
|View full text |Cite
|
Sign up to set email alerts
|

The mutational spectrum of single base-pair substitutions in mRNA splice junctions of human genes: Causes and consequences

Abstract: A total of 101 different examples of point mutations, which lie in the vicinity of mRNA splice junctions, and which have been held to be responsible for a human genetic disease by altering the accuracy of efficiency of mRNA splicing, have been collated. These data comprise 62 mutations at 5' splice sites, 26 at 3' splice sites and 13 that result in the creation of novel splice sites. It is estimated that up to 15% of all point mutations causing human genetic disease result in an mRNA splicing defect. Of the 5'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
885
6
17

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,194 publications
(932 citation statements)
references
References 56 publications
24
885
6
17
Order By: Relevance
“…Thus in the JCaM1 DNA, the inability to initiate the correct excision of intron 7 at the 5' splice site could explain the absence of complete lck transcript: the exon 7 is no longer recognized as such and is thereby excluded from the mature mRNA. In agreement with Krawczak et al (1992) who observed that it is always the upstream exon immediately preceding the defect that was removed from the mature mRNA, we reported here that exon 7 is skipped as a consequence of a point mutation in intron 7. By means of COS cells transfected with minigenes from the Jurkat or JCaM1 cells, we could indeed demonstrate the critical role played by this mutation in the splicing mechanism.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus in the JCaM1 DNA, the inability to initiate the correct excision of intron 7 at the 5' splice site could explain the absence of complete lck transcript: the exon 7 is no longer recognized as such and is thereby excluded from the mature mRNA. In agreement with Krawczak et al (1992) who observed that it is always the upstream exon immediately preceding the defect that was removed from the mature mRNA, we reported here that exon 7 is skipped as a consequence of a point mutation in intron 7. By means of COS cells transfected with minigenes from the Jurkat or JCaM1 cells, we could indeed demonstrate the critical role played by this mutation in the splicing mechanism.…”
Section: Discussionsupporting
confidence: 93%
“…Numerous studies have reported splicing defects leading to either absence or reduction of the mature mRNA. In particular the study by Krawczak et al (1992) reports more than 100 point mutations in the vicinity of exon/intron splices junctions which result in such splicing defects. Among these mutations, 60% take place at the 5' splice site and more than half lead to exon skipping.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] To detect a genomic DNA mutation responsible for the skipping of HS1 exon A, we synthesized primers for HS1 exon Aspecific PCR, and conducted PCR/SSCP analysis for the patient and normal controls. However, no DNA fragment showed variations on electrophoresis (data not shown).…”
Section: Detection Of Transcripts Encoding the Aberrant Hs1 In The Pamentioning
confidence: 99%
“…Aberrant splicing is mostly caused by the mutation at the splicing consensus sequence of exon-intron boundary, and, to a lesser extent, by a point mutation within the skipped exon. [33][34][35][52][53][54][55] However, there are several reports of exon skipping without any mutations in the sequence around the skipped exon. [56][57][58][59][60] Besides, a mutation in an intron away from an exon-intron boundary results in a defect in splicing.…”
Section: Genes and Immunitymentioning
confidence: 99%
“…For example, relative to each other, different splice forms may have altered mRNA stability or translational efficiency or encode proteins with modified localization or function [6,19,36]. Significantly, around 15% of disease-causing mutations in human genes are point mutations in the vicinity of mRNA splice junctions, supporting the hypothesis that alternative splicing can have major effects on gene function [10,18]. Understanding the function of all rice genes, including alternative splice forms, will be invaluable toward improving rice and other grass species to meet human needs.…”
Section: Introductionmentioning
confidence: 99%